Effect of systemic anticoagulants on fracture healing in rats tibia - Tanrisever, Murat; Can, Umit Koray; Istek, Ozmen; Ozcan, Erhan Cahit; Eroksuz, Hatice; Karabulut, Burak; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Healthy Control group (n=8): no procedure was applied sidues eleaseddirectyor iniretlyto the nvirnment a during the four-week experimental setup. Sham group (n=8): useserious problemsin nature. DMT residuesmxedwhthe quaticfractures wereenvironment created inadversely the rightaffec tibiasaquatic of the organismssubjects andby surgical methods and the fractures were fixed with Kirshner iseffeciscarrietoumansthroughthefoodchainInthis wires in this group and all anticoagulant group the Apixaban Group (n=8) received 5 mg/kg of apixaban; the smutase(SOD),catalase CAT) andglutathoneperoxidase Rivaroxaban Group (n=8) received 3 mg/kg of rivaroxaban; the Edoxaban Group (n=8) received 3 mg/kg of edoxaban; and the ereinvestigatedResults weredetermnedusingELISAkis iio sign fican dif erence was observed in GSH levels and SOD tivities compa red to contro Stati ti call y significant differences ere observedbetween dereases in CATandGPxactivitieand creases inTBARS levels SPSS240 packageprogramone-way
Keywords: PX) causedby dimethoae (DMT)pesticidein Pleptodactylus; l (P < 05). Adem & aacute;s; el grupo Dabigatr & aacute;n (